Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

For each equation, give the solution or determine that there are no solutions.

(a) [tex]\(5(2+w)-w=10+4(w+1)\)[/tex]

(b) [tex]\(2(x-1)+8=6(2x-4)\)[/tex]


Sagot :

Sure, let's solve each equation step-by-step.

### Part (a):
Solve the equation [tex]\(5(2+w) - w = 10 + 4(w+1)\)[/tex]

1. Distribute the numbers inside the parentheses:
[tex]\[ 5(2+w) = 5 \cdot 2 + 5 \cdot w = 10 + 5w \][/tex]
[tex]\[ 4(w+1) = 4 \cdot w + 4 \cdot 1 = 4w + 4 \][/tex]

2. Rewrite the equation:
[tex]\[ 10 + 5w - w = 10 + 4w + 4 \][/tex]

3. Combine like terms:
[tex]\[ 10 + 4w = 14 + 4w \][/tex]

4. Move all variables to one side and constants to the other:
Subtract [tex]\(4w\)[/tex] and 14 from both sides:
[tex]\[ 10 + 4w - 4w = 14 + 4w - 4w \][/tex]
[tex]\[ 10 = 14 \][/tex]

Since [tex]\(10\)[/tex] is not equal to [tex]\(14\)[/tex], this means there are no solutions for this equation.

### Part (b):
Solve the equation [tex]\(2(x-1) + 8 = 6(2x-4)\)[/tex]

1. Distribute the numbers inside the parentheses:
[tex]\[ 2(x-1) = 2 \cdot x - 2 \cdot 1 = 2x - 2 \][/tex]
[tex]\[ 6(2x-4) = 6 \cdot 2x - 6 \cdot 4 = 12x - 24 \][/tex]

2. Rewrite the equation:
[tex]\[ 2x - 2 + 8 = 12x - 24 \][/tex]

3. Combine like terms:
[tex]\[ 2x + 6 = 12x - 24 \][/tex]

4. Move all variables to one side and constants to the other:
Subtract [tex]\(12x\)[/tex] and 6 from both sides:
[tex]\[ 2x - 12x + 6 = -24 \][/tex]
[tex]\[ -10x + 6 = -24 \][/tex]
Subtract 6 from both sides:
[tex]\[ -10x = -30 \][/tex]

5. Solve for [tex]\(x\)[/tex]:
[tex]\[ x = \frac{-30}{-10} = 3 \][/tex]

So, the solution for this equation is [tex]\(x = 3\)[/tex].

### Summary
(a) There are no solutions for the equation [tex]\(5(2+w) - w = 10 + 4(w+1)\)[/tex].

(b) The solution for the equation [tex]\(2(x-1) + 8 = 6(2x-4)\)[/tex] is [tex]\(x = 3\)[/tex].